Floristic composition and diversity of mangroves in selected sites in the province of Antique, Panay Island, Philippines. - Balinas, Lucelle V.
The study covers the floristic composition of true mangrove species and the mangroves's diversity on selected sites in the province of Antique during the time of sampling only
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Mangroves -- Antique, Panay Island Philippines